Cluster-Randomized Clinical Trial Examining the Impact of Platelet Function Testing on Practice: The Treatment With Adenosine Diphosphate Receptor Inhibitors. (June 2015) - Wang, Tracy Y.; Henry, Timothy D.; Effron, Mark B.; Honeycutt, Emily; Hess, Connie N.; Zettler, Marjorie E.; Cohen, David J.; Baker, Brian A.; Berger, Peter B.; Anstrom, Kevin J.; Angiolillo, Dominick J.; Peterson, Eric D.
Abstract : Background—: Little is known about how clinicians use platelet function testing to guide choice and dosing of adenosine diphosphate receptor inhibitor (ADPri) therapy in routine community practice. Methods and Results—: The Treatment With Adenosine Diphosphate Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events After Acute Coronary Syndrome (ACS)—Prospective, Open Label, Antiplatelet Therapy Study (TRANSLATE-POPS) was a cluster-randomized trial in which 100 hospitals were assigned access to no-cost platelet function testing versus usual care for acute myocardial infarction patients treated with percutaneous coronary intervention. In both arms, ADPri treatment decisions were left up to the care team. The primary end point was the frequency of ADPri therapy adjustment before discharge. Secondary end points included 30-day rates of major adverse cardiovascular events and Global Utilization of Streptokinase and Tissue Plasminogen Activator for Occluded Coronary Arteries–defined bleeding events. Platelet function testing was performed in 66.9% of patients treated in intervention sites versus 1.4% of patients in usual care sites. Intervention arm patients were more likely to have ADPri therapy adjustment than usual care patients (14.8% versus 10.5%, P =0.004; odds ratio 1.68, 95% confidence interval 1.18–2.40); however, there were no significant differences in 30-day major adverse cardiovascular events (4.8% versus 5.4%, P =0.73; odds ratio 0.94, 95% confidence interval 0.66–1.34) or bleeding (4.3% versus 4.2%, P =0.33; odds ratio 0.86, 95% confidence interval 0.55–1.34). One-year outcomes were also not significantly different between groups. An as-treated analysis showed higher incidence of ADPri therapy adjustment among intervention arm patients who received platelet function testing than untested usual care arm (16.4% versus 10.2%, P <0.0001), but no significant differences in major adverse cardiovascular events or bleeding. Conclusions—: TRANSLATE-POPS found that when clinicians routinely used platelet function testing, they were more likely to adjust their choice or dosing of ADPri therapy; yet with few changes in therapy overall, significant differences in clinical outcomes were not seen. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01088503. Abstract : Supplemental Digital Content is available in the text.